Optimization of Image Compression algorithms using DWT- DCT method (International Journal of Engineering and Computer Science, 2017)
Information is generated at very high speed in today’s Digital Era. Images have vast share in Information generated, so it’s important to reduce the image file size for storage and effective communication. Image compression technique helps in reducing storage and bandwidth requirement for transmission. Optimization of Image compression algorithms is the basic crux of this paper. DCT is most popularly used lossy image compression technique. It has disadvantage that at higher compression ratio the quality of image is lost. DCT is applied to set of images, followed by DWT. The resultant compression metrics are calculated and visual quality of image is analyzed. Experimental analysis shows reduction in storage space requirement and effective optimization using different methodology.